Pengaruh Pemberian Kalsium Terhadap Panjang Kranium Fetus Tikus Putih (Rattus Norvegicus) Setelah Pemberian Etanol - Reni Zuraida; Nurlis Mahmud; Efrida Warganegara; Radinal Mauludi (Fakultas Kedokteran Universitas Lampung, 2012)
Calcium is an essential element in the human body primarily on bone metabolism processes. Calcium is needed to activate the osteoblast in producing bone matrix. Calcium metabolism in human body could be inhibited by ethanol. Someone who consumes ethanol will suffer hypocalcemia. Consequently activating process of the osteoblast producing of bone matrix will be imbalanced and bone structure will be abnormal. The purpose of this study was to determine the effect of calcium supplementation on the length of white rat fetus cranium in organogenesis phase of Sprague Dawley strain that had been treated by ethanol. This study uses an experimental research design using 20 rats (Rattus norvegicus) of Sprague Dawley strain pregnant females aged 10-16 weeks which randomly selected were divided into five groups. The results showed that the average cranium length from analysis of one way ANOVA p value = 0.000. Post Hoc LSD cranium length with five groups compared with each other p = 0.000. Can be concluded that the existence of the effect of calcium supplementation on the length of white rat (Rattus norvegicus) fetus cranium that had been treated by ethanol